Effects of wearable resistance training on linear sprinting and jumping abilities in healthy populations: a systematic review and three-level meta-analysis - Wei, Chen; Zhou, Zihan; Wang, Fuhai; Zhang, Xiaoquan (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to systematically evaluate and analyze the effects of weighted resistance training (WRT) on linear sprinting and jump abilities in healthy populations through a three-level meta-analysis.MethodsWe systematically searched five databases, including PubMed, Web of Science, The Cochrane Library, SPORTDiscus, and Embase, for randomized controlled trials (RCTs) investigating the effects of WRT on linear sprinting and jumping abilities, with the search conducted from database inception until 1 May 2025. The quality of the literature was assessed using the Cochrane ROB2 tool and the Physiotherapy Evidence Database (PEDro) scale, whereas the quality of evidence was evaluated using GRADE. A three-level random effects model was implemented in R for the meta-analysis, along with an assessment of publication bias. Hedges’ g and its 95% confidence intervals (CIs) were calculated for evaluation. Publication bias was examined using funnel plots and multilevel Egger’s regression tests.ResultsTen studies, comprising 256 participants, were included. The meta-analysis results indicated that WRT significantly improved linear sprinting ability (95% CI: −0.558 to −0.027, p < 0.05), while no significant effect was observed on jumping ability (95% CI: −0.067 to −0.545, p = 0.118). Subgroup analyses revealed that WRT positively effected 10-m linear sprinting performance (g = −0.393, 95% CI -0.784 to −0.002, p = 0.049). Specifically, trunk WRT (g = −0.554, 95% CI -1.013 to −0.096, p = 0.020) and weights ≤10% of body mass (BM) (g = −0.495, 95% CI -0.884 to −0.107, p = 0.014) significantly improved sprinting performance. The GRADE assessment indicated that the quality of evidence regarding the effects of WRT on linear sprinting and jumping abilities was low.ConclusionThese findings suggest that WRT with trunk load and weights ≤10% of BM can enhance start acceleration (0–10 m) during linear sprinting. However, WRT did not significantly improve jumping ability.